PENERAPAN PENILAIAN AUTENTIK PENDIDIKAN AGAMA ISLAM DI SEKOLAH TERINTEGRASI DENGAN PERILAKU KEAGAMAAN DI MASYARAKAT SISWA SMP NEGERI 2 BANJARMANGU BANJARNEGARA - sadiah, Umi Halimatus; Majid, Abdul; Fatiatun, Fatiatun (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
This research discusses the implementation of Authentic Assessment in Islamic Religious Education at an integrated school in relation to the religious behavior of students at SMP Negeri 2 Banjarmangu. This research utilizes a qualitative method. Data was collected through observation, interviews, and documentation. The analysis was conducted using qualitative descriptive analysis techniques, which encompass written or oral data from individuals and observed behaviors. The purpose of this study is to provide a comprehensive overview of the actual conditions. The results of this study indicate that Islamic education in SMP Negeri 2 Banjarmangu has an influence on the religious behavior of students in society. This is achieved through the cultivation of religious practices, such as congregational morning prayer (shalat dhuha), congregational noon prayer (shalat dzuhur), Quranic recitation, recitation of prayers before and after studying, as well as greeting and showing respect to others. Additionally, teachers provide advice and motivation regarding religious behavior to students and set a good example through their own actions. The implementation of authentic assessment in Islamic education at the school also contributes to enhancing the religious behavior of students in SMP Negeri 2 Banjarmangu. Authentic assessment is carried out through assessment guidelines, such as the development of Lesson Implementation Plans (RPP) for class VIII and the preparation of teaching modules for class VII. These two classes follow different curricula, namely the Merdeka curriculum for class VII and the 2013 curriculum for class VIII. The implementation of religious instruction involves several stages, including preparation, execution, the use of instructional media, and evaluation.